(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Students, who are expected to have pedagogical competence in addition to professional competence, social competence and personal competences, are also expected not clueless. Acquiring these competencies absolutely requires adequate teaching materials. The purpose of this study is to develop the materials of Indonesia Language and Literature Learning Plan lesson course based on web centric course through the model of Jere Confrey that are qualified and effective . This study is conducted by using the approach of ISO / IEC TR 19796-1: 2005 about e-Learning System Development. Data collection techniques use validity questionnaires and students questionnaires. Data analysis is carried out by qualitative analysis. This study is expected to have valid and practical results.